PENGARUH LATIHAN MENGGUNAKAN TARGET TERHADAP AKURASI PASSING PEMAIN SEPAK BOLA SSB SUNGAI LIMAU - NABIL, NABIL HAMDANI SYAFANDRA; Andri Gemaini; Ridho Bahtra; Alimuddin (Jurnal IKEOR, 2026)
Abstract: The problems in the research include low accuracy of football passing and players do not yet have good passing attributes in the internal game so they cannot provide maximum play and often make mistakes. The purpose of the research is to see the effect of passing training using targets on the passing accuracy of SSB Sungai Limau football players. The type of research is quantitative research with a quasi-experimental method. The research method used in this study is a pretest-posttest one group design. The research location is the Sungai Sariak field at the Sungai Limau SSB location, precisely behind the Sungai Limau police station in May - June 2025. The research population is all 31 Sungai Limau SSB players, while the sample uses purposive sampling of 15 people. The data collection technique is the accuracy of football passing. The data analysis technique is descriptive percentage and hypothesis testing (t-test). The results of the study were obtained in the pretest was in the fairly good category with an average value of 5.53 and the posttest was in the good category with an average of 6.93. There was a 25% increase in passing accuracy from pretest to posttest. The t-test results produced a t table < t table, namely 5.5 < 2.13, so it can be concluded that H0 is accepted, namely there is an effect of training using targets on the passing accuracy of SSB Sungai Limau football players. Keywords: Practice, Target, Passing Accuracy, Football. Abstrak: Permasalahan pada penelitian diantaranya rendahnya akurasi passing sepakbola dan pemain belum mempunyai atribut passing yang baik pada internal game sehingga belum dapat memberikan permainan yang maksimal dan sering melakukan kesalahan.. Tujuan penelitiannya yaitu untuk melihat pengaruh latihan passing menggunakan target terhadap akurasi passing pemain sepakbola SSB Sungai Limau Jenis penelitian yaitu penelitian kuantitatif dengan metode quasi experimental. Metode penelitian yang digunakan dalam penelitian ini adalah pretest- posstest one group design. Tempat penelitian di lapangan Sungai Sariak di tempat SSB Sungai Limau tepatnya dibelakang polsek sungai limau pada bulan Mei – Juni 2025.